Study the Influence of Treatment Interruptions in the Radical Irradiation of Breast Cancer - Azam, Alia A.; Oraby, Ahmed H.; Awad, Ibrahim A.; Attalla, Ehab M. (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Hypofractionated radiotherapy (HFRT) in breast cancer treatment regimen (40 Grey /15 fractions/3 weeks) is more convenient for patients, especially those coming from remote areas to radiotherapy facilities and for healthcare providers, than conventional fractionation (50 Gy/25 fractions/5weeks). So the effect of radiotherapy interruption on treatment outcome (loco-regional control (LRC)& overall survival (OS)) during hypofractionated schedule is the issue of our study. Materials and Methods: We studied retrospectively 174 female patients with breast cancer who received PORT at the Clinical Oncology & Nuclear Medicine Department, Faculty of Medicine, Mansoura University, Egypt, from January-2012 to December-2016. We determined the treatment outcome (OS&LRC) from the follow-up (FU) of the studied patients, as the patient still survived or died, and recurrence till now occurred or not, and were estimated with the Kaplan-Meier (K-M) method and Logrank test, respectively. Then we calculated surviving fraction (SF) and tumor control probability (TCP) with regard to biologically effective dose (BED), for all patients, using breast cancer radiobiological parameters. Results: When comparing patients without radiotherapy gap with patients with radiotherapy gaps, the results showed a decrease in LRC rate in patients with radiotherapy treatment interruptions by 15 % (P=0.019, a significant value), but no detrimental effect on OS because of the very limited number of the studied patients. Curves of the relationship between (SF&OTT) and (TCP&OTT) confirmed the detrimental effect of unscheduled gap during radiotherapy fractions on the treatment outcome. Also we found a significant-P value for (marital status, start day of radiotherapy fractions, time, number, and duration of gaps); it means these factors affect LRC during radiotherapy interruptions.Conclusions: Interruptions during postoperative hypofractionated irradiation of 7breast cancer (40 Gy/15 fractions/3weeks) should be avoided and if they are inevitable, they should not be prolonged more than two days, as they will adversely affect the treatment outcome (LRC).